Social-emotional development: From theory to practice. Issue 6 (1st November 2016) - Malti, Tina; Noam, Gil G.
Abstract: This theoretical article aims to introduce a new conceptual framework for the understanding and enhancement of child and adolescent social-emotional development (SED). We first elaborate on a taxonomy to classify core dimensions of SED and make a case for its importance. Next, we introduce our developmental approach to the study of SED and elaborate as to why there is a need to connect developmental theory and research systematically with the use of social-emotional assessment tools. We briefly describe the holistic student assessment (HSA) as an example of such a tool through which children, teachers, and caregivers report on dimensions of SED. The HSA generates individual, classroom, and school-wide profiles of SED. How such profiles can be used to inform intervention planning and implement developmentally sensitive strategies to promote SED and intervene psychopathology will also be discussed. We conclude with reflections on how our developmental approach to understanding and assessing SED relates to Bildung-Psychology as we argue for a renewed focus on the 'whole child' and a broadened view of educational attainment.